1990
DOI: 10.1007/bf02129064
|View full text |Cite
|
Sign up to set email alerts
|

Osteopenia and phenylketonuria

Abstract: Trabecular bone mineral content was assessed by quantitative computed tomography in eleven young adults with phenylketonuria who had been treated from early childhood with a diet restricted in natural protein and supplemented with amino acids, minerals and vitamins. There was a significant reduction in the bone mineral content of patients compared with the normal population. Prospective studies are indicated in younger patients to ensure optimum bone mineralisation is achieved by adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 3 publications
1
16
0
1
Order By: Relevance
“…However, most previous studies assessing bone quality in PKU (Allen et al 1994;Al-Qadreh et al 1998;Carson et al 1990;McMurry et al 1992;Schwahn et al 1998) did not evaluate bone mineral density (BMD) by the gold-standard method of DXA (Genant et al 1999), reported heterogeneous patient populations (Barat et al 2002;Perez-Duenas et al 2002;Schwahn et al 1998), or comprised only a small number of patients (Barat et al 2002;Schwahn et al 1998).…”
Section: Introductionmentioning
confidence: 98%
“…However, most previous studies assessing bone quality in PKU (Allen et al 1994;Al-Qadreh et al 1998;Carson et al 1990;McMurry et al 1992;Schwahn et al 1998) did not evaluate bone mineral density (BMD) by the gold-standard method of DXA (Genant et al 1999), reported heterogeneous patient populations (Barat et al 2002;Perez-Duenas et al 2002;Schwahn et al 1998), or comprised only a small number of patients (Barat et al 2002;Schwahn et al 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Higher intake of food phenylalanine correlated to a BTM ratio favoring resorption (p-value ¼ 0.017) while better compliance with medical food correlated to a BTM ratio favoring formation (p-value ¼ 0.056) suggesting following diet is critical. DXA showed normal BMD for age in all subjects and a mean total BMD Z-score of 0.045 (range À1.9-2.3) contradicting low BMD found in previous studies (Carson et al 1990;Zeman et al 1999;Perez-Duenas et al 2002;Koura et al 2011) but in line with more recent reports (Demirdas et al 2015;Geiger et al 2016). We defined low BMD by ISCD criteria (Z-score <À2) instead of alternative definitions used in previous studies (Demirdas et al 2015).…”
Section: Discussionmentioning
confidence: 58%
“…Other studies also find no correlations between dietary calcium, protein, and energy intake and BMD, BMD Z-score or BTM in patients of any age (Carson et al 1990;McMurry et al 1992;Hillman et al 1996;Modan-Moses et al 2007;Lage et al 2010). Positive correlations have been reported, however, between total calcium and phosphorus intake and BMD Z-score (PerezDuenas et al 2002) and calcium and protein from medical food and spine BMD (Geiger et al 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Carson et al 42 , utilizando o método de tomografia computadorizada de espinha lombar, verificaram uma significativa redução do conteúdo mineral ósseo trabecular de 4 dos 11 pacientes com fenilcetonúria estudados, com faixa etária entre 19 a 34 anos. Os autores verificaram correlação positiva entre o conteúdo mineral ósseo e a proporção adequada de calorias, proteínas, cálcio e cobre da dieta.…”
Section: Fenilcetonúria E Perda óSseaunclassified